Effect of Temperature, Time and Amount of Alkaline Treated Cotton Seaweed (ATS) Products Dried in a Dryer Oven on Product Quality - Mochammad Masud; Mohammad Effendi; Miftachul Huda (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2019)
Eucheuma cottonii seaweed contains carrageenan, which is used as an ingredient for the food and beverage industry. This must be processed first by an alkaline process and then dried to become chips known as alkaline treated cotton chips (ATC) products. The process of drying seaweed was done using an oven dryer using heat energy that can be adjusted to the drying time, temperature and number of products so that the quality of the dried products of seaweed products that have been processed into Alkaline Treated Cotton Seaweed (ATS) to be used as an advanced product becomes ATC (Alkali Treated Cotton Chips). The results of this study aim to find out the optimal value of temperature, drying time and the amount of ATS to get output from ATC in accordance with SNI 8170: 2015 standard and received by the customer. Based on the results of the study, it was found that the minimum significant drying process for moisture content was 12.10% at level 2, 1 kg weight, level 2 temperature 70 oC with level 3 drying time 400 minutes. Whereas the maximum gel strength is 910 gram / cm2 at level 1, weight 0.5 kg, level 2 temperature 70 oC with level 2 drying time 320 minutes.